2023
DOI: 10.3390/ijms24076332
|View full text |Cite
|
Sign up to set email alerts
|

LTR Retroelements and Bird Adaptation to Arid Environments

Abstract: TEs are known to be among the main drivers in genome evolution, leading to the generation of evolutionary advantages that favor the success of organisms. The aim of this work was to investigate the TE landscape in bird genomes to look for a possible relationship between the amount of specific TE types and environmental changes that characterized the Oligocene era in Australia. Therefore, the mobilome of 29 bird species, belonging to a total of 11 orders, was analyzed. Our results confirmed that LINE retroeleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(76 reference statements)
1
0
0
Order By: Relevance
“…Thirdly, our study highlighted an LTR-RT burst in the wild ancestors of domestic ducks, and the evolutionary signatures, such as SNP density, around intact-LTR regions. Previous studies have shown that LTR-RT burst was related to the environment adaption in birds (45), and here we found that LTR-RT burst might be involved in duck domestication. For example, some Pekin or domestic specific intact-LTRs potentially regulate the expression of their neighbor genes associated with animal domestication, including IGF2BP1 for increasing body size (13), MITF for feather color changing (13), PCDH15 for adapting environment (35) and ANXA5 for enhancing productive ability (33).…”
Section: Discussionsupporting
confidence: 74%
“…Thirdly, our study highlighted an LTR-RT burst in the wild ancestors of domestic ducks, and the evolutionary signatures, such as SNP density, around intact-LTR regions. Previous studies have shown that LTR-RT burst was related to the environment adaption in birds (45), and here we found that LTR-RT burst might be involved in duck domestication. For example, some Pekin or domestic specific intact-LTRs potentially regulate the expression of their neighbor genes associated with animal domestication, including IGF2BP1 for increasing body size (13), MITF for feather color changing (13), PCDH15 for adapting environment (35) and ANXA5 for enhancing productive ability (33).…”
Section: Discussionsupporting
confidence: 74%